Perancangan Sistem Pelayanan Administrasi Desa Berbasis Mobile (Studi Kasus: Desa Karangrena, Maos, Cilacap) - Alfin Andrias Wardoyo; Muhammad Fachrie (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Currently, village governments are still facing inadequate and inefficient village administration systems in providing services to the community. The incompetence and inefficiencies of village administration systems can be seen from the numerous complaints from residents. People have complained about complicated, time-consuming village management procedures with unclear requirements. Recent technological developments in practice can be utilized to solve existing problems in public services, such as the use of mobile applications. In other words, technological advances, especially in the field of mobile applications, can be a solution to improve the quality of public services, including village level administration services. The purpose of this research is to design a mobile-based village administration service system to facilitate administration services at the village level. The waterfall model is the system development method used in this research. The Dart programming language is utilized within the Flutter framework to develop the system. Black box testing is conducted to test the functionality of the system being built. The test results demonstrate that the system runs well as expected, thus successfully implementing a Village Administration Service System that leverages mobile technology.